2015
DOI: 10.1371/journal.pone.0125295
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Study of Novel Gene Silencer Pyrrole-Imidazole Polyamide Targeting Human TGF-β1 Promoter for Hypertrophic Scars in a Common Marmoset Primate Model

Abstract: We report a preclinical study of a pyrrole-imidazole (PI) polyamide that targets the human transforming growth factor (hTGF)-β1 gene as a novel transcriptional gene silencer in a common marmoset primate model. We designed and then synthesized PI polyamides to target the hTGF-β1 promoter. We examined effects of seven PI polyamides (GB1101-1107) on the expression of hTGF-β1 mRNA stimulated with phorbol 12-myristate 13-acetate (PMA) in human vascular smooth muscle cells. GB1101, GB1105 and GB1106 significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…2; Table 1), including a pyrrole-imidazole polyamide drug that blocks transcription of the TGFB1 target gene (Yao et al 2009;Chen et al 2010;Matsuda et al 2011;Washio et al 2011;Igarashi et al 2015), antisense RNAs that target TGFB1 or TGFB2 mRNAs for degradation (Hau et al 2009;Vallieres 2009;Schlingensiepen et al 2011), antibodies against TGF-b ligands or receptors that block ligand -receptor engagement, and many small molecule ATP-mimetic TbRI kinase inhibitors (Fig. 2).…”
Section: Drugs That Block Tgf-b Signalingmentioning
confidence: 99%
“…2; Table 1), including a pyrrole-imidazole polyamide drug that blocks transcription of the TGFB1 target gene (Yao et al 2009;Chen et al 2010;Matsuda et al 2011;Washio et al 2011;Igarashi et al 2015), antisense RNAs that target TGFB1 or TGFB2 mRNAs for degradation (Hau et al 2009;Vallieres 2009;Schlingensiepen et al 2011), antibodies against TGF-b ligands or receptors that block ligand -receptor engagement, and many small molecule ATP-mimetic TbRI kinase inhibitors (Fig. 2).…”
Section: Drugs That Block Tgf-b Signalingmentioning
confidence: 99%
“…Pinpointing the mutations which predispose a patient to develop pathological scars offers the possibility of pre-operative planning and primary prophylaxis, thus sparing the need for reintervention or costly and timeconsuming treatments ahead. Furthermore, understanding the molecular basis of scarring is the first step in creating molecular treatment options for keloid scars, as seen with TGF-1 promoter silencing therapy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda et al showed that PI polyamides accumulated in nuclei of kidney cells in rats and were maintained for about two weeks without any drug delivery system [135,136]. Recently, Igarashi et al [137] studied the possible clinical applications of PI polyamides using a primate model. They developed an ointment including a PI polyamide targeting human transforming growth factor beta (TGF-β) 1 and tested for hypertrophic scars in marmosets.…”
Section: Development Of Novel Drugsmentioning
confidence: 99%
“…They developed an ointment including a PI polyamide targeting human transforming growth factor beta (TGF-β) 1 and tested for hypertrophic scars in marmosets. The PI polyamide bound to keratinocyte nuclei in marmosets and suppressed hypertrophic scarring without any side effects [137]. These reports are fundamental evidence for the clinical application of PI polyamides and increasing interest in their use for AR and some AR collaborative TFs, such as OCT1 and ETS family genes.…”
Section: Development Of Novel Drugsmentioning
confidence: 99%